Preparation of leukoreduced whole blood for transfusion in austere environments; effects of forced filtration, storage agitation, and high temperatures on hemostatic function. Issue 6 (June 2018) - Sivertsen, Joar; Braathen, Hanne; Lunde, Turid Helen F.; Spinella, Philip C.; Dorlac, Warren; Strandenes, Geir; Apelseth, Torunn O.; Hervig, Tor A.; Kristoffersen, Einar K.
Abstract : BACKGROUND: Damage control resuscitation principles advocate the use of blood to treat traumatic hemorrhage. Hemorrhage is a leading cause of preventable death on the battlefield, but making blood components available far forward presents logistical challenges due to shelf life and storage requirements. Whole blood simplifies logistics and enables collection in the field but can cause leukocyte-related transfusion reactions. A field-adapted leukoreduction system must be fast and safe, and storage of whole blood should preserve hemostatic function. METHODS: Blood was collected using Imuflex WB-SP and leukoreduced at 0, 150, or 300 mm Hg. Additional bags were stored at 4°C for 21 days unagitated, mixed daily, agitated or head-over-heel rotated, at 22°C for 3 days, or 32°C for 2 hours. Hematology, coagulation, CD62P/CD42b, thromboelastography (TEG)/thromboelastometry (ROTEM), and Multiplate was performed. RESULTS: Filtration time was 35 ± 1, 14 ± 0, and 9 ± 0 minutes at 0, 150, and 300 mm Hg, respectively. One of 10 units at 150 mm Hg and 4 of 11 at 300 mm Hg had residual whole blood cells greater than 5.0 × 10 6 per unit. One of 11 at 300 mm Hg had platelet recovery of less than 80%. Hemolysis was less than 0.2%. Filtration decreased thromboelastography/thromboelastometry and Multiplate aggregation response. Stored at 4°C, α and MA/MCF moderately decreased regardless of mixing. Significant loss of aggregation response and increased CD62P expression was seen by Day 10. By Day 3, storage at 22°C caused loss of most aggregation. Two-hour storage at 32°C did not significantly affect hemostatic capacity. CONCLUSION: Forced filtration reduced leukoreduction time, but increased residual whole blood cells reduced hemostatic function. Aggregation response deteriorated early in storage, while viscoelastic assays decreased more gradually. Mixing showed no benefits. LEVEL OF EVIDENCE: Diagnostic study, level IV.